Public Policy Towards R&D in Oligopolistic Industries - Leahy, Dermot; Neary, J. Peter (American Economic Review, 1997)
We consider the free-market and socially optimal outcomes in a general oligopoly model with many firms which first engage in R&D and then compete in either output or price. Strategic behavior by firms tends to reduce output, R&D, and welfare and so justifies higher subsidies except when R&D spillovers are low and firms' actions are strategic substitutes. It also reduces the benefits of R&D cooperation. Moreover, policies to encourage cooperation are likely to be redundant (since it is always privately profitable) and simulations suggest that the welfare cost of lax competition policy is high.